The development of patient suicide post-vention guidelines for psychiatry trainees and supervisors. (October 2020) - Henry, Jessica; Ramages, Meagan; Cheung, Gary
Objectives: Patient suicide is one of the most stressful events for psychiatrists and psychiatry trainees. However, there is often a lack of consistent guidance and support available to clinicians, including post-vention. The aim of this paper is to describe the development of a resource that could support psychiatry trainees following patient suicide. Methods: Following a literature review, we adapted two US patient suicide post-vention guidelines to reflect local processes and support systems available by consulting a number of key stakeholders in the training programme and district health boards. Results: The first part of the post-vention guidelines included procedural processes such as the serious incident review process and reporting to coroner's office. The second part included a checklist for trainee, supervisor, local training facilitator and director of training according to the following time frame: first 24 hours, first 1–2 weeks and following months. Conclusions: Post-vention guidelines and teaching about patient suicide and its effects could improve the training experience of psychiatry trainees and facilitate the development of resilience as they progress through training.